SHAPING VALUES IN CRISIS: NONPROFIT ORGANISATIONAL CULTURE AND ITS EVOLVING ROLE IN THE 21ST CENTURY - Ганна Кайтанджян (Економіка та суспільство, 2025)
This review article explores the evolving nature of organisational culture within nonprofit organisations (NPOs), especially in the face of crisis, societal transformation and digitalisation. Drawing upon a wide range of theoretical frameworks and recent research, including comparative and regional studies in nonprofit management and leadership, the article identifies key cultural dimensions that define NPOs, discusses leadership styles shaping those cultures and examines how recent global and regional crises have accelerated cultural shifts. By emphasising the interplay between culture, leadership (situational, adaptive, participative and ethical) and organisational outcomes such as commitment, job satisfaction and proactivity, this paper contributes to a growing body of literature that views culture as a dynamic and strategic organisational asset. It calls for greater contextualisation in nonprofit cultural studies, with special attention to post-crisis environments, digital workspaces and the influence of cross-sector leadership experiences.